The efficacy and safety of procedural sedoanalgesia performed by emergency physicians in the emergency department of Piacenza. A single-center retrospective observational study. - Borio, Giorgia; Poggiali, Erika; Vercelli, Andrea; Fabrizi, Enrico (Acta Biomedica Atenei Parmensis, 2024)
Procedural sedation (PSA) is a common procedure performed in the emergency department (ED) and represents a fundamental skill for emergency physicians (EP). However, only a few studies have looked at the overall success and incidence of complications of PSA administered by non-anesthesiologists. This study aims to examine the effectiveness and safety of PSA administered by EPs in the ED. Methods: This is a single-center retrospective observational study of patients undergoing PSA in the ED of Piacenza (Emilia-Romagna, Italy) between January 1, 2022, and May 21, 2023, for electric cardioversion, bone dislocation or fracture reductions, and pacing. Patients’ demographic data, nil per os time, doses and combination of drugs, vital signs, and incidence of adverse events (AEs) were recorded. Results: Three hundred and seventeen patients were enrolled. The most often used intravenous (IV) combination was fentanyl plus midazolam (45%), followed by midazolam alone (41%). In 314 patients (99%), PSA was successfully provided. AEs occurred in 28 out of 317 patients (8.5%). The most common complication was hypoxia (3.1%). No patient required intubation. All the AEs have been successfully managed by EPs. No deaths were recorded. Conclusions: Our results indicate that EPs can safely and effectively administer PSA in the ED. We suggest the creation of an Italian SPA registry to promote collaboration amongst Italian EDs and the sharing of drug protocols to standardize patients’ pathways.